2003
DOI: 10.1002/cncr.11255
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic detection and evaluation of morphologic and biochemical changes in early human oral carcinoma

Abstract: BACKGROUNDUnderstanding the development and progression of head and neck squamous cell carcinoma is key in the quest for the early diagnosis and prevention of this type of malignancy. The current study correlated early biochemical and histologic changes in oral tissue with spectral features in fluorescence, reflectance, and light scattering spectra acquired in vivo to diagnose early stages of oral malignancies.METHODSA total of 91 tissue sites from 15 patients with varying degrees of malignancy (normal, dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
227
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(240 citation statements)
references
References 37 publications
10
227
0
3
Order By: Relevance
“…Also, collagen cross-link decomposition, associated with neoplasia development, 18 contributes to the reduction of fluorescence signal intensity. Mü ller et al 21 have shown that oral cavity carcinoma is accompanied by an increase in epithelial thickness, which reduces the depth of penetration of excitation light that reaches stromal collagen, thus reducing its contribution to the total signal.…”
Section: Tumor Locationmentioning
confidence: 99%
“…Also, collagen cross-link decomposition, associated with neoplasia development, 18 contributes to the reduction of fluorescence signal intensity. Mü ller et al 21 have shown that oral cavity carcinoma is accompanied by an increase in epithelial thickness, which reduces the depth of penetration of excitation light that reaches stromal collagen, thus reducing its contribution to the total signal.…”
Section: Tumor Locationmentioning
confidence: 99%
“…[5][6][7][8][9][10] Raman and infrared vibrational spectroscopic techniques have also been exploited for investigating eukaryotic and prokaryotic cells. [11][12][13][14][15] As can be seen from the literature, among these two methods, infrared, probably due to its higher sensitivity, has been most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…However, the stronger peaks in these spectra correspond to collagen and NADH. 26 The intensity ratios of these peaks for normal and malignant samples are plotted in Figure 5. It can be seen that there is substantial difference in the ratio of concentration of collagen to NADH in malignancy, as shown by earlier workers also.…”
Section: Resultsmentioning
confidence: 99%